2010
DOI: 10.1016/j.socscimed.2009.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Functional declines, social support, and mental health in the elderly: Does living in a state supportive of home and community-based services make a difference?

Abstract: This study examines how acute and chronic stresses associated with functional declines in seniors and their spouses are moderated by their informal and formal support contexts. In the United States, states vary greatly in their support for home and community-based services (HCBS) for seniors with disabilities. This state-to-state variation allowed us to examine mental health effects of living in a society supportive of HCBS for the oldest old, who are at high risk for low or declining functions in daily activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 41 publications
5
70
0
Order By: Relevance
“…This finding was in line with the results of Foote et al's research [38] which indicates that there is a significant relationship between hope, self-esteem, and social support in MS patients. Furthermore, the results of the current research are consistent with Muramatsu et al [39] and Zielinski et al [40] which illustrated that there is a positive relationship between social support and hope. In line with the results of the current research, Gibbons et al [24] showed that the dynamic supportive-expressive therapy is effective in the community mental health system and depression.…”
Section: Discussionsupporting
confidence: 91%
“…This finding was in line with the results of Foote et al's research [38] which indicates that there is a significant relationship between hope, self-esteem, and social support in MS patients. Furthermore, the results of the current research are consistent with Muramatsu et al [39] and Zielinski et al [40] which illustrated that there is a positive relationship between social support and hope. In line with the results of the current research, Gibbons et al [24] showed that the dynamic supportive-expressive therapy is effective in the community mental health system and depression.…”
Section: Discussionsupporting
confidence: 91%
“…For example, past studies have linked to the US Census, Dartmouth Atlas of Health Care, American Hospital Association, Centers for Disease Control, RAND Center for Population Health and Health Disparities and others. 27,[39][40][41][42][43] …”
Section: Available and Future Data Linkagesmentioning
confidence: 99%
“…Olagunju et al (2015) came to the same conclusions in a Nigerian elderly community; and Muramatsu,Yin and Hedeker (2010) in North-American elderly. Loneliness -a psychosocial dimension highly interconnected with social support -has been associated to severe depressive symptoms and to elevated depression levels in the follow-up on Dutch elderly (Holvastet al, 2015).…”
Section: Resultsmentioning
confidence: 56%
“…The study by Olagunju, Olutoki, Ogunnubi and Adeyemi (2015) showed that the severity of depression in elderly people is significantly correlated with social support availability from significant people and family. Muramatsu, Yin and Hedeker (2010) also determined that there is a predominant role of informal support from the family (other than from the spouse) and from friends in the elderly's low levels of depression. In conclusion, we consider that these results make sense because it is natural that those elderly who perceive themselves as having social support in a stage of life in which they frequently experience adverse events (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation